2017
DOI: 10.3393/ac.2017.33.5.201
|View full text |Cite
|
Sign up to set email alerts
|

<italic>Salmonella enteritis</italic>: A Rare Cause of Adult Intussusception

Abstract: Intussusception is a relatively rare condition in the adult population and is commonly secondary to a malignant process. Eight to twenty percent of cases of adult intussusception are thought to be idiopathic. In children, infection has been proven to precipitate intussusception in the absence of any other cause. We present a rare case of intussusception in a healthy adult patient secondary to salmonella infection and discuss infection as a potential explanation for a proportion of the cases of adult intussusce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Another finding in our study was that the presence of diarrhea or fever in patients ultimately diagnosed with intussusception may have led to misdiagnosis as acute gastroenteritis. Previous studies have reported that bacterial enteritis significantly increases the relative risk of intussusception ( 29 , 30 ). An increased risk of intussusception was found after Salmonella, E. coli, Shigella , and Campylobacter infection ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another finding in our study was that the presence of diarrhea or fever in patients ultimately diagnosed with intussusception may have led to misdiagnosis as acute gastroenteritis. Previous studies have reported that bacterial enteritis significantly increases the relative risk of intussusception ( 29 , 30 ). An increased risk of intussusception was found after Salmonella, E. coli, Shigella , and Campylobacter infection ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is considered to be important to decide the treatment strategy according to the degree of symptoms; in cases with few symptoms, non-invasive reduction, such as endoscopy and barium examination, was a first choice and incases with strong symptoms, surgery was performed with careful consideration for bowel ischemia. Moreover, it is considered necessary to evaluate the mucosal surface for distinguishing the condition from special intussusception, such as parasites [22,23]. We believe that minimal bowel resection or early endoscopic observation after surgery was desirable.…”
Section: Discussionmentioning
confidence: 99%